Avaliação externa: implicações e contribuições para a prática avaliativa do professor - Pereira, Kalina Elis Leitão (2023)
This research, with a qualitative approach, was driven by concerns related to the effects that large-scale assessments, notably the São Paulo School Performance Assessment System and the Assessment of Learning in Process, can have on school dynamics and the influences that these evaluations have the potential to raise the evaluation practice of teachers in a state public school in São Paulo. Thus, our general objective was to analyze whether the evaluation practices of a group of teachers in the 5th year of elementary education at a state school in São Paulo are influenced by external evaluations. The specific objectives of this study were: a) to describe the context, objectives and uses, with regard to the characteristics of large-scale external evaluations (instruments, evaluation routines, forms of feedback); b) identify the teachers' evaluation practices (instruments, evaluation routines, feedback forms); c) compare the identified characteristics of the external assessments with the assessment practices carried out by the professors, in order to verify possible similarities and differences between the two dimensions of the assessment; and d) indicate possible training needs of teachers regarding their assessment practices. The present research used, as a methodology for data collection, concepts of documentary research and to reveal the subjectivities in the conceptions of evaluations of the participants, the semi-structured interviews. The interpretations, analyzes and reflections on the data collected in the documentary research and in the semistructured interview were anchored in the content analysis. In the school where the research took place, the use of simulated evaluation instruments, external evaluations and the need to invest in continuing education on evaluation in a critical-reflexive perspective stand out, so that the study brings contributions on how to reframe the teachers' evaluation practices